Perspectives on Nordic Working Life Research - Karlsson, Jan Ch. (Nordic Journal of Working Life Studies, 2013)
Welcome to this Thematic Issue on Perspectives on Nordic Working Life Research! It is perhaps not that surprising that a journal called Nordic Journal of Working Life Studies contains many discussions about “Nordic Models”: What is the Nordic Welfare State Model? What has happened to it lately? Is there still one? Has there ever been one? What about the Nordic Industrial Relations Model—is it on its way to be abandoned? And the Nordic Labor Market Model? Or the Nordic Work Environment Model? In contrast, in the Thematic Issue part of this issue of NJWLS Nordic working life research itself is discussed. Editing the issue has led me to some (self)critical reflections on Nordic working life research—or perhaps rather reflections on the self-image of Nordic working life researchers. We often say that two of the cornerstones of Nordic working life research are the assumption that there is a positive correlation between employee autonomy at work and higher productivity, and that our research tradition is different from those found in other geographical areas (and, implicitly, probably better). Being part of the Nordic tradition, I too have claimed both, but I now think both needs to be qualified and critically discussed. Or rather, the first needs to be qualified and the consequences of the other critically evaluated (...)